Visual Improvement in Retinal Vein Occlusion Patient Who Had Intravitreal Bevacizumab with and without Laser Photocoagulation - Marita Febiana; Iwan Sovani; M Rinaldi Dahlan; Feti Karfiati (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: Intravitreal bevacizumab (IVB) appears to be an effective and safe drug for reducing macular edema and improving visual acuity secondary to RVO. Grid photocoagulation to macular edema caused by BRVO significantly improved long-term visual prognosis. In CRVO, reduced the angiographic evidence of macular edema, but did not lead to improvement in the vision of treated eyes. Methods: an observational, retrospective study from medical record of patients RVO underwent IVB and combined treatment at Cicendo National Eye Center conducted between January and December 2012. A total of 49 eyes from 49 patients met the inclusion criteria. Data was compiled on demographic characteristics, pre and postoperative visual acuities. The main outcome was proportion of visual gain in 1 month after therapy. Result: All patients (49 eyes) completed the 1 months follow-up with 17 patients BRVO who had treatment IVB and 11 patients with combined treatment. And 14 patients CRVO who had treatment IVB and 7 patients had combined treatment. The proportion of BRVO and CRVO eyes have the same visual improvement in IVB and combined treatment groups (BRVO 58.8% vs 72.7%, p=0.120 and CRVO 57.1% vs 57.1%, p=1.000). Conclusion: There was no significant difference in the proportion of visual improvement between IVB and combined treatment groups in BRVO and CRVO at one months follow up. Keywords: branch retinal vein occlusion, central retinal vein occlusion, intravitreal bevacizumab, laser photocoagulation